Categorizing the Relationship between Terrorism and the Media (Annual of the Faculty of Philosophy in Skopje, 2018)
This paper explains the delicate relationship between the media and terrorism inorder to achieve a better understanding of the relationship between the two entities. In thispaper, we will study both how publicity benefits terrorists, and how the media benefitsfrom the acts of terrorists. The present paper will attempt to answer the following questions:How can we rethink the sensationalist coverage of terrorism and stop providing terroristsa free media platform? What kinds of relationships exist between terrorist groups andthe media? To what degree can the media itself be held responsible for providing terrorismwith the “oxygen of publicity”? Is it possible for the media to objectively report about terroristswithout promoting their actions and instigating fear?The purpose of this paper will be focused on the relationship between media coverageand terror attacks themselves, raising the question of whether increased coverage hasan effect on the increased number of terrorist attacks.
Keywords: MEDIA; TERRORISM; REPORTING; COMMUNICATION